2017
DOI: 10.1159/000454725
|View full text |Cite
|
Sign up to set email alerts
|

Familial 5q12.3 Microdeletion: Evidence for a Locus Associated with Epilepsy

Abstract: The clinical use of array comparative genomic hybridization (array CGH) has allowed the identification of very rare deletion and duplication disorders, such as 5q12 deletion syndrome (OMIM 615668) described as a contiguous gene deletion syndrome of chromosome 5q12. Chromosome microdeletions including band 5q12 have rarely been reported and have been associated with different phenotypes showing postnatal growth restriction, intellectual disability, epileptic seizures, hyperactivity, and ocular abnormalities. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Previous reports have shown that the 5q12 deletions are associated with a wide range of clinical characteristics, such as postnatal growth retardation, intellectual disability, developmental delay, hyperactivity, nonspecific ocular defects, facial dysmorphism, and, epilepsy [2][3][4][5][6] (Table 2). The size of 5q12 heterozygous deletions varies considerably between 0.9 and 17.2 Mb, and they all occurred de novo, except for the 2.8 Mb inherited deletion associated with epilepsy reported by Gnan and colleagues [6] (Figure 3). In contrast to previous reports, our patient exhibits only modest growth retardation, an angioma of the right lower eyelid, and an ovarian cyst.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous reports have shown that the 5q12 deletions are associated with a wide range of clinical characteristics, such as postnatal growth retardation, intellectual disability, developmental delay, hyperactivity, nonspecific ocular defects, facial dysmorphism, and, epilepsy [2][3][4][5][6] (Table 2). The size of 5q12 heterozygous deletions varies considerably between 0.9 and 17.2 Mb, and they all occurred de novo, except for the 2.8 Mb inherited deletion associated with epilepsy reported by Gnan and colleagues [6] (Figure 3). In contrast to previous reports, our patient exhibits only modest growth retardation, an angioma of the right lower eyelid, and an ovarian cyst.…”
Section: Discussionmentioning
confidence: 99%
“…These patients have overlapping clinical features making it difficult to delineate a specific clinical phenotype mainly due to the variable size of the deleted segments between 0.9 to 17.2 Mb. Clinical features range from postnatal growth retardation, intellectual disability, behavioral abnormalities (hyperactivity), nonspecific ocular defects, facial dysmorphism, and epilepsy [2][3][4][5][6]. Here, we report the case of a child from non-consanguineous and healthy parents, which came to our attention for postnatal growth retardation.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, Chiari 1 malformation has been reported for the first time in our case. Some genes that are included in the deleted region are known to be expressed in the CNS and that could potentially cause the anomalies [5]. More studies are needed to demonstrate the effects of the other genes in 5q11.…”
mentioning
confidence: 99%